KONDISI DAN POTENSI WISATA ALAM DI WILAYAH GUNUNG SAWAL KABUPATEN CIAMIS, JAWA BARAT Conditions and Potency of Ecotourism in Sawal Mountains Region Ciamis Regency, West Java - Dian Diniyati (Lambung Mangkurat University-Indonesia, 2014)
The purpose of the research is to describe the condition and the potency of ecotourism surrounding Sawal Mountain Sanctuary (SMGS) forest. The research was conducted on January 2008 at Sanding Taman village, Panjalu sub district, Pasir Tamiang village Cihaurbeuti sub district and Darmacaang village Cikoneng sub district. The respondents consisted of 76 tourists and 48 communities who were selected purposively, took census to 22 traders. Data were collected by interview using questionnaires and by observation. Collected data were analyzed by quantitative and qualitative descriptive. The result showed that the infrastructures which supported all studied objects were very limited. Tourism attractions proposed still origin, less artificial additions, such as natural scenery (water fall and forest), champing, clean and fresh air, and swimming. The visitors were dominated by young, small families and foreigners. Each year, the three tourism objects were estimated earned 3,016,000 IDR, 27,300,000 IDR and 2,880,000 IDR for Curug Tilu, Curug Tujuh and Batu Cakra respectively. These financial values could be increased if the three tourism objects were managed well. One of the urgent efforts has to be considered was deciding the form of management and who will manage for.Keywords: Sawal Mountain Sanctuary (SMGS), ecotourism, tourist characteristic, financial value.